The Effect of Infant Massage on Nutritional Status and IGf-1 of Malnourished Babies Aged 6-12 Months - Sudarmi Sudarmi; I Gusti Ayu Putu Sri Wahyuni (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
Malnourished and poor nutrition are still a health center problem in Indonesia. A good nutritional intake can often not be fulfilled by a child, including due to various factors. Baby massage is a touch therapy that is carried out on baby so that it can provide assurance of ongoing body contact, maintain a feeling of security in the baby and strengthen the parent's love cord with the baby.  The purpose of this study was to analyze the effectiveness of baby massage by mothers on improving the nutritional status of baby with malnutrition aged 6-12 months. This study used a quasi-randomized pre-test and post-test control group design. Samples were 48 babies aged 6-12 months with malnutrition divided into two groups (intervention and control group). This research was carried out for 3 months. Results showed that stimulation of baby massage is effective in increasing mean IGF-1 levels for malnourished baby aged 6-12 months, namely the average IGF-1 level in the pre-intervention group for baby massage by 1.37 ± 1.00, showed a significant increase (p = 0.003). Whereas in the control group showed a significant increase (p = 0.001) with the average IGF-1 pretreatment level was 3.37 ± 8.15. The results of the case and control group analysis showed significant differences in mean IGF-1 levels (p = 0.002) or (p <0.05). Baby massage is effective in increasing nutritional status and IGF-1 in baby aged 6-12 months. Babies’ Mother and health provider are recommended to apply baby massage to improve nutritional status of malnourished babies.